Elevated Blood Pressure in Rat Offspring with Induced Intrauterine Growth Restriction: A Systematic Review - Patridina, Geneung; Prasetyorini, Nugrahanti (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Intrauterine growth restriction (IUGR), often caused by placental insufficiency, is a significant obstetric issue associated with adverse long-term health outcomes, including hypertension. This systematic review investigates the association between induced IUGR and elevated blood pressure in rat offspring. Material and Methods: A systematic search of PubMed, SpringerLink, and the Cochrane Library was conducted on February 10, 2023, following PRISMA guidelines. Studies were included if they involved rat models of placental insufficiency-induced IUGR with documented birth weight reduction and blood pressure measurements compared to a control group. Data were extracted for meta-analysis using Review Manager 5. Results: Eight studies met the inclusion criteria. Meta-analysis revealed a significant increase in both mean arterial pressure (MAP) (Mean Difference: 9.84, 95% CI: 2.69–16.99, p = 0.007) and systolic blood pressure (SBP) (Mean Difference: 13.09, 95% CI: 7.87–18.32, p < 0.00001) in IUGR offspring compared to controls. The increase in SBP was more pronounced in male offspring than in females. Conclusion: Induced IUGR in rats leads to significantly elevated blood pressure, with a greater effect observed in males. Rat models provide valuable insights into the developmental origins of hypertension, though they may overestimate the effect and not fully replicate the human condition. The endothelin system and sex hormones are implicated in this sexually dimorphic response.